Simple digital circuits for direct-to-digital sensors - Piao, Jiaming (Nanyang Technological University, 2021)
A new smart direct-to-digital photo sensor system circuit design was proposed which included photodiode, transimpedance amplifier circuit and voltage-controlled CMOS ring oscillator. This dissertation focused on the circuit design and transistor level simulation. Consequently, a transimpedance amplifier was created to convert the photocurrent generated by photodiode into photovoltage signal for oscillator control. In the meantime, the pulse counter receives time-varying-frequency signal and converts the light-modulated frequency in a truly digital signal/code that can easily generate an analog voltage. Hence, the photodiode output is directly converted into a digital signal with no need of complex ADC circuit. Simulation and tests were performed by LTSpice to verify the operation of the studied circuits. The absence of ADC greatly simplifies the overall camera/pixel array circuit, decreases the number of transistors, and contributes to pixel unit circuit downsizing.